Legal Protection for TikTok Creators Against Unauthorized Content Re-uploads - Bago, Ester Intensis; Sudirman, Lu; Agustianto, Agustianto (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2025)
The rapid growth of TikTok presents new challenges in copyright protection, particularly regarding unauthorized content re-uploads. This study aims to analyze the effectiveness of copyright protection for TikTok creators in Batam City using an empirical juridical approach through interviews and literature studies. The findings indicate that while Law No. 28 of 2014 on Copyright provides a strong legal foundation, its implementation faces challenges such as regulatory gaps, low legal awareness among creators, and weak enforcement on digital platforms. TikTok has copyright protection policies, but its reporting system remains ineffective in addressing violations. The Directorate General of Intellectual Property (DJKI) of the Riau Islands has conducted awareness campaigns; however, these efforts need to be reinforced with clearer regulations and stronger collaboration between the government, digital platforms, and creators. Therefore, increasing legal awareness and strengthening policies are necessary to optimize copyright protection for digital content creators. [Pertumbuhan pesat TikTok menghadirkan tantangan baru dalam perlindungan hak cipta, khususnya terkait dengan pengunggahan ulang konten tanpa izin. Studi ini bertujuan untuk menganalisis efektivitas perlindungan hak cipta bagi para kreator TikTok di Kota Batam dengan menggunakan pendekatan yuridis empiris melalui wawancara dan studi literatur. Temuan menunjukkan bahwa meskipun Undang-Undang No. 28 Tahun 2014 tentang Hak Cipta memberikan dasar hukum yang kuat, implementasinya menghadapi sejumlah tantangan seperti celah regulasi, rendahnya kesadaran hukum di kalangan kreator, dan lemahnya penegakan hukum di platform digital. TikTok memiliki kebijakan perlindungan hak cipta, namun sistem pelaporannya masih belum efektif dalam menangani pelanggaran. Direktorat Jenderal Kekayaan Intelektual (DJKI) Provinsi Kepulauan Riau telah melakukan kampanye penyuluhan, namun upaya tersebut perlu diperkuat dengan regulasi yang lebih jelas serta kolaborasi yang lebih solid antara pemerintah, platform digital, dan para kreator. Oleh karena itu, peningkatan kesadaran hukum dan penguatan kebijakan menjadi hal yang penting untuk mengoptimalkan perlindungan hak cipta bagi para kreator konten digital.]